Mettere in gioco i servizi ecosistemici: limiti e opportunità di nuovi scenari sociali ed economici - Riccardo Santolini; Elisa Morri; Rocco Scolozzi (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
Ecosystems are an irreplaceable support for a region’s quality of life, thanks to the goods and services that they provide (ecosystem services). These ecosystem services can be assessed in economic terms, considering the economic weight of natural capital in resources management and in landscape planning (e.g. strategic plans, rural development plans) and recognizing the crucial role of those territories that have natural resources and a sustainable strategic planning. This approach can be translated in a territorial equalization between those territories that consume natural resources and those that produce them.